The Role of Primary Teacher in the Midst of the Opportunities and Challenges Faced in the Fourth Industrial Revolution - Ghovinda Fitra Wijaya; Wiputra Cendana; Mark Ayres (Actual Insight, 2026)
The fourth industrial revolution has brought about numerous opportunities and challenges in the field of education, particularly for primary teachers. According to a few studies, the role of teachers in this era is to facilitate learning. However, the data revealed that many teachers continued to struggle with understanding the context of education in the fourth industrial revolution age, as well as their function in this field. The goals of this study are to learn about the opportunities and challenges that primary teacher experienced throughout the fourth industrial revolution era, particularly regarding the Internet. Also, recognize the teacher's role in the fourth industrial revolution. The findings suggest that teachers have more opportunities in the fourth industrial era, including easier access to knowledge and learning sources; also, the learning process can be much more interesting, seamless, dynamic, engaging, and fun. The primary teacher encounters several problems, including inadequate facilities, diverse student personalities, and the teacher's difficulty adapting to new technology. In the fourth industrial revolution period, teachers in primary school should be more than just as facilitators for their students such as motivator, demonstrator, trainer, and instructor. It is recommended that the following writer take particular notes in order to do in-depth study.